1987
DOI: 10.1017/s0043174500079376
|View full text |Cite
|
Sign up to set email alerts
|

Breakage of Seed Dormancy of Field Pennycress (Thlaspi arvense) by Growth Regulators, Nitrate, and Environmental Factors

Abstract: Effects of ethylene, gibberellins, kinetin, nitrate, light, and temperature, each alone or combined with other factors, were studied on the germination of dormant seed of field pennycress (Thlaspi arvenseL. # THLAR). Treated seed were incubated at a range of constant temperatures, at temperatures alternating daily between 12 and 22 C (12 h each), or at 12 C followed by transfer to 22 C. No germination ocurrred in water under any conditions. When applied in the dark KNO3had no effect on germination under any of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…It is also possible, however, that an increase in respiration rate is just one of the earliest and more easily measured changes in metabolic activity induced by the osmotic effect of the nitrate on water up-take. The well-established correlation between increases in respiration rate and tissue hydration during seed imbibition is consistent with this hypothesis, A comparison of the effect of various nitrate salts on the germination of Thiaspi arven.se (Saini et al, 1987) showed that germination was induced by the nitrate ion, and that the associated cation had little or no effect. This conclusion agreed with similar germination studies on A. fatua (Sharma et al, 1976) and other species (Roberts and Smith 1977), and was consistent with the observation that, while KNO-, induced 100% germination, an equimolar solution of KCI had no promotive effect.…”
Section: Discussionsupporting
confidence: 73%
“…It is also possible, however, that an increase in respiration rate is just one of the earliest and more easily measured changes in metabolic activity induced by the osmotic effect of the nitrate on water up-take. The well-established correlation between increases in respiration rate and tissue hydration during seed imbibition is consistent with this hypothesis, A comparison of the effect of various nitrate salts on the germination of Thiaspi arven.se (Saini et al, 1987) showed that germination was induced by the nitrate ion, and that the associated cation had little or no effect. This conclusion agreed with similar germination studies on A. fatua (Sharma et al, 1976) and other species (Roberts and Smith 1977), and was consistent with the observation that, while KNO-, induced 100% germination, an equimolar solution of KCI had no promotive effect.…”
Section: Discussionsupporting
confidence: 73%
“…However, earlier maturing varieties are needed to ensure that pennycress can be harvested early, allowing for full-season soybean production. Seed dormancy also is an issue, 25 , 26 as is common in many weed species; we have observed highly variable germination rates in preliminary field trials. Pennycress oil and protein meal are not currently suitable for animal or human consumption.…”
Section: Introductionmentioning
confidence: 68%
“…Other studies on the dormancy of freshly matured field pennycress have reported conflicting results (NAPPO 2003). Field pennycress dormancy was broken by a period of cooling (12 C) followed by a transfer to a warmer temperature (22 C), or by a combination of temperature fluctuations, light, nitrate, and growth regulators (Saini et al 1987). Canadian researchers reported no seed dormancy in plants grown in a glasshouse, whereas seed from field-grown plants were mostly dormant (Hume 1984).…”
Section: Resultsmentioning
confidence: 99%